PERAN GREEN TRUST DALAM MEMEDIASI PENGARUH GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE BEHAVIOR - Utami, Ni Made Jayanti; Pramudana, Komang Agus Satria (E-Jurnal Manajemen, 2017)
This research was conducted in order to test the role of trust in mediating the effects of green green green perceived value of the product purchase behavior on organic vegetables in Bali Bunda Cafe . This study using purposive sampling technique. The sample size used in this study were 55 respondents using path analysis technique (path analysis). These results indicate that green perceived value has a positive and significant impact on the green purchase behavior on products organic vegetables in Bali Bunda Cafe , green perceived value has a positive and significant impact on the green trust in the products organic vegetables, green trust has a positive and significant impact on the green purchase behavior on organic vegetable products in the Bali Bunda Cafe , green trust significantly mediates the effects of green perceived value of the green purchase behavior on organic vegetable products in the Bali Bunda Cafe.
Keywords: green perceived value; green trust; green purchase behavior; organic vegetable products